2001
DOI: 10.1179/026708301101509287
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of aluminium alloys after HNO3/HF–NaOH–HNO3/HF pretreatment

Abstract: The effect of a pretreatment sequence on several aluminium alloys was examined by X-ray photoelectron spectroscopy and SEM. The pretreatment consisted of vapour degreasing followed by a three step sequence comprising 1 min immersions in (a) nitric acid -hydrofluoric acid solution, (b) sodium hydroxide solution and (c) a 1 or 5 min immersion in nitric acid -hydrofluoric acid as in step (a). Following each pretreatment step the alloy panels were rinsed in tap water for 1 min. The surfaces of aluminium alloys 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 15 publications
(3 reference statements)
0
53
0
Order By: Relevance
“…Previous studies have indicated that Al, Fe and Mn may be removed preferentially from these particles during deoxidation in HNO 3 -based deoxidizers. 21,22 Etching of the surrounding matrix is also evident in Fig. 1(a) in the form of scalloping.…”
Section: Deoxidationmentioning
confidence: 85%
“…Previous studies have indicated that Al, Fe and Mn may be removed preferentially from these particles during deoxidation in HNO 3 -based deoxidizers. 21,22 Etching of the surrounding matrix is also evident in Fig. 1(a) in the form of scalloping.…”
Section: Deoxidationmentioning
confidence: 85%
“…This is attributed, in some instances, to electrochemically active surface layers which readily undermine the polymeric topcoat, 41,46,47 and in other cases to poor adhesion of the topcoat to the basic residual oxides left on the surface after alkaline cleaning. 17,18,48,49 The rapid growth of filaments in this instance is attributed to the poor adhesion of the polyurethane to the alkaline-cleaned surface of AA2024-T3, which comprises basic oxides and silicates, 49 although reactive surface layers cannot be ruled out.…”
Section: Corrosion On the Matrixmentioning
confidence: 96%
“…Deoxidation etches the surface, providing a mechanical key for adhesion of the polyurethane to the substrate metal, including "scalloping" and also "texturing" down to the tens of nanometers scale, 49 which was recently attributed to localized etching around impurities. 50 The progress of a filament therefore requires the generation of a greater amount of corrosion product to lift the polyurethane, resulting in deeper attack of the metal.…”
Section: Corrosion On the Matrixmentioning
confidence: 99%
“…7.8(a) and (b). 183,184,191,192 The residual oxides on these surfaces are less than 10 nm in thickness, and refl ect the chemistry of the deoxidizer through absorbed surface species. On the other hand, low etch rate deoxidizers such as HNO 3 and a low etch rate rare earth deoxidizer (see next section) leave a thicker oxide that seems to facilitate cerium conversion coating deposition and performance.…”
Section: Surface Cleaning Processes and Coating Effectivenessmentioning
confidence: 99%
“…In particular they aim to produce a surface with the minimal amount of Cu, although Cu build-up is inevitable even for low-Cu containing alloys. 184 As Cu facilitates the deposition of the rare earth coating, these processes, particularly those that contain nitrate, slow the deposition process. There have been a number of studies that have used mineral acids that do not dissolve Cu, but leave a heavy Cu-smut on the surface such as phosphoric or sulphuric acids.…”
Section: Boehmite Formation In Solutions Containing Rare Earthsmentioning
confidence: 99%